2015
DOI: 10.1007/s11307-015-0887-8
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Exchange Saturation Transfer (CEST) MR Technique for Liver Imaging at 3.0 Tesla: an Evaluation of Different Offset Number and an After-Meal and Over-Night-Fast Comparison

Abstract: Purpose To explore whether Chemical Exchange Saturation Transfer (CEST) MRI can detect liver composition changes between after-meal and over-night-fast statuses. Procedures 15 healthy volunteers were scanned on a 3.0 T human MRI scanner in the evening 1.5–2 hour after dinner and in the morning after over-night (12-hour) fasting. Among them seven volunteers were scanned twice to assess the scan-rescan reproducibility. Images were acquired at offsets (n=41, increment=0.25ppm) from −5 to 5ppm using a turbo spin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(47 citation statements)
references
References 48 publications
3
44
0
Order By: Relevance
“…Additionally, to further improve this black blood T1ρ relaxometry sequence, additional techniques can be incorporated, including more robust measurement (22,(40)(41)(42)(43) and faster data sampling and reconstruction (44). Recently, the feasibility of CEST (chemical exchange saturation transfer) technique for liver imaging has been demonstrated (38,45). MR Elastography technique has also been further validated for assessing diffused liver diseases (46,47).…”
Section: Bdl Is a Well Established Model For Liver Fibrosis Researchmentioning
confidence: 99%
“…Additionally, to further improve this black blood T1ρ relaxometry sequence, additional techniques can be incorporated, including more robust measurement (22,(40)(41)(42)(43) and faster data sampling and reconstruction (44). Recently, the feasibility of CEST (chemical exchange saturation transfer) technique for liver imaging has been demonstrated (38,45). MR Elastography technique has also been further validated for assessing diffused liver diseases (46,47).…”
Section: Bdl Is a Well Established Model For Liver Fibrosis Researchmentioning
confidence: 99%
“…Very few studies have attempted glycoCEST in humans at 3T as motion of organs, and B 0 spatial inhomogeneity and temporal changes present a challenge to quantification. One study has demonstrated liver glycogen reduction after fasting . Another has shown that muscle glycogen can be assessed at 3T with proper frequency correction using the WASSR method .…”
Section: Discussionmentioning
confidence: 99%
“…One study has demonstrated liver glycogen reduction after fasting. 48 Another has shown that muscle glycogen can be assessed at 3T with proper frequency correction using the WASSR method. 8 The DvNav-based prospective frequency and first order shim measurement and correction presented here could improve accuracy of muscle glycogen CEST measurements.…”
Section: Discussionmentioning
confidence: 99%
“…114 On the other hand, the Cr level is low in the liver, and glycoCEST may be more useful, and is indeed being tried in humans. 196,197 However, glucose signals will overlap with those of glycogen and, when using MTR asym , NOE effects may also be mixed in. Thus, further editing will likely be needed to cleanly separate out these effects in the leg and the liver.…”
Section: Cest Studies Of Creatine (Crcest) and Glycogen (Glycocest)mentioning
confidence: 99%